Divergence in female damselfly sensory structures is consistent with a species recognition function but shows no evidence of reproductive character displacement. Issue 23 (20th November 2018) - Barnard, Alexandra A.; Masly, John P.
Abstract: Males and females transmit and receive signals prior to mating that convey information such as sex, species identity, or individual condition. In some animals, tactile signals relayed during physical contact between males and females before and during mating appear to be important for mate choice or reproductive isolation. This is common among odonates, when a male grasps a female's thorax with his terminal appendages prior to copulation, and the female subsequently controls whether copulation occurs by bending her abdomen to complete intromission. It has been hypothesized that mechanosensory sensilla on the female thoracic plates mediate mating decisions, but is has been difficult to test this idea. Here, we use North American damselflies in the genus Enallagma (Odonata: Coenagrionidae) to test the hypothesis that variation in female sensilla traits is important for species recognition. Enallagma anna and E. carunculatum hybridize in nature, but experience strong reproductive isolation as a consequence of divergence in male terminal appendage morphology. We quantified several mechanosensory sensilla phenotypes on the female thorax among multiple populations of both species and compared divergence in these traits in sympatry versus allopatry. Although these species differed in features of sensilla distribution within the thoracic plates, we found no strong evidence of reproductive character displacement among the sensilla traits we measured in regions of sympatry. Our results suggest that species‐specific placement of female mechanoreceptors may be sufficient for species recognition, although other female sensory phenotypes might have diverged in sympatry to reduce interspecific hybridization. Abstract : Physical touch is a relatively overlooked sensory modality that could have important effects on mating decisions, particularly in odonates (dragonflies and damselflies). We quantified and compared female sensory structures across multiple sympatric and allopatric populations of two recently diverged, hybridizing damselfly species. Our goals were to (a) quantify variation in mechanoreceptor traits as in inroad for dissecting the mechanistic basis of tactile discrimination and (b) test for patterns of reproductive character displacement (RCD) in these species.